Closure in Biblical narrative - Zeelander, Susan. (Biblical Interpretation Series, 2012)
There has been much discussion of narrative aspects of the Bible in recent years, but the ends of biblical narratives - how the ends contribute to closure for their stories and how the ending strategies affect the whole narrative - have not been studied comprehensively. This study shows how the writers and editors of short narratives in Genesis gave their stories a sense of closure (or in a few cases, the sense of non-closure). Multiple and sometimes unexpected, forms of closure are identified; together these form a set of closural conventions. This contribution to narrative poetics of the Hebrew Bible in the light of source criticism will also be valuable to those who are interested in narrative and in concepts of closure.